International core curriculum for capsule endoscopy training courses - Fernandez-Urien, I (2017)
Capsule endoscopy (CE) has become a first-line noninvasive tool for visualisation of the small bowel (SB) and is being increasingly used for investigation of the colon. The European Society of Gastrointestinal Endoscopy (ESGE) guidelines have specified requirements for the clinical applications of CE. However, there are no standardized recommendations yet for CE training courses in Europe. The following suggestions in this curriculum are based on the experience of European CE training courses directors. It is suggested that 12 hours be dedicated for either a small bowel capsule endoscopy (SBCE) or a colon capsule endoscopy (CCE) course with 4 hours for an introductory CCE course delivered in conjunction with SBCE courses. SBCE courses should include state-of-the-art lectures on indications, contraindications, complications, patient management and hardware and software use. Procedural issues require approximately 2 hours. For CCE courses 2.5 hours for theoretical lessons and 3.5 hours for procedural issued are considered appropriate. Hands-on training on reading and interpretation of CE cases using a personal computer (PC) for 1 or 2 delegates is recommended for both SBCE and CCE courses. A total of 6 hours hands-on session- time should be allocated. Cases in a SBCE course should cover SB bleeding, inflammatory bowel diseases (IBD), tumors and variants of normal and cases with various types of polyps covered in CCE courses. Standardization of the description of findings and generation of high-quality reports should be essential parts of the training. Courses should be followed by an assessment of trainees' skills in order to certify readers' competency.